Feasibility Study of the Actuator Mechanism using Deformation of Ferromagnetic Martensite by Magnetic Field - SASAKI, Kazuaki; KATO, Hiroyuki (Transactions of the Japan Society of Mechanical Engineers Series A, 2004)
The present paper provides a quantitative analysis on the variant change of ferromagnetic martensite driven by the magnetization energy under magnetic field. The feasiblity study of the actuator mechanism using the magnetic-field induced strain is given. The model predicts an upper limit of output power of the actuator : the maximum output force of NiMnGa shape memory alloy is estimated as less than 1 MPa : the output energy is 2 000 times smaller than that of conventional NiTi shape memory alloys driven by heat.